2018
DOI: 10.4088/jcp.17m11585
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With a Ghrelin Agonist in Outpatient Women With Anorexia Nervosa

Abstract: ClinicalTrials.gov identifier: NCT01642550.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 34 publications
(34 reference statements)
0
42
0
Order By: Relevance
“…In AN not only central [ 77 ] and peripheral [ 78 ] ghrelin expression is increased, but also ghrelin signaling and modulation are impaired as indicated by a delayed or absent postprandial decrease of ghrelin [ 64 , 91 ], the inability to suppress GH secretion adequately after glucose digestion [ 101 ] or the insufficiency of glucose elevation after exogenous ghrelin application [ 119 ], suggesting ghrelin resistance in AN ( Figure 1 ). Noteworthy, exogenous ghrelin (by raising ghrelin to supraphysiological levels) or ghrelin receptor agonists still might be able to improve the course of AN by stimulating appetite and reducing gastric discomfort leading to an increase of energy intake and body weight [ 100 , 123 , 127 ]. Since these data are derived from small pilot studies, these effects should be corroborated—or refuted—in larger clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AN not only central [ 77 ] and peripheral [ 78 ] ghrelin expression is increased, but also ghrelin signaling and modulation are impaired as indicated by a delayed or absent postprandial decrease of ghrelin [ 64 , 91 ], the inability to suppress GH secretion adequately after glucose digestion [ 101 ] or the insufficiency of glucose elevation after exogenous ghrelin application [ 119 ], suggesting ghrelin resistance in AN ( Figure 1 ). Noteworthy, exogenous ghrelin (by raising ghrelin to supraphysiological levels) or ghrelin receptor agonists still might be able to improve the course of AN by stimulating appetite and reducing gastric discomfort leading to an increase of energy intake and body weight [ 100 , 123 , 127 ]. Since these data are derived from small pilot studies, these effects should be corroborated—or refuted—in larger clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…These findings should be followed up in patients with AN as well. Very recently, a study investigated the effects of relamorelin (subcutaneously daily over a period of four weeks), a ghrelin agonist, in an outpatient cohort ( n = 10–12/group) of AN showing a significant acceleration of gastric emptying as well as a trend towards an increase of body weight (+0.9 kg vs. 0.3 kg in the control group, p < 0.07) [ 127 ]. Again, larger follow up studies are needed.…”
Section: Effects Of Exogenous Ghrelin In Anorexia Nervosamentioning
confidence: 99%
“…An RCT with the ghrelin receptor agonist, ulimorelin, demonstrated symptomatic improvements over placebo in 23 hospitalized patients with diabetic gastroparesis (159). The ghrelin agonist, relamorelin, was recently tested in an RCT of 22 chronic, stable patients with AN (BMI 17.7 ± 0:4) (160), where 3 out of 10 patients dropped out due to an increased hunger sensation. Gastric emptying was shortened by the ghrelin agonist; however, there was no significant weight gain during 4 weeks of treatment (160).…”
Section: Ghrelinmentioning
confidence: 99%
“…We measured MAT in women randomized to either four weeks of a GHS1a receptor agonist (relamorelin) (n=7) or placebo (n=11) and found that although L4 MAT was similar in both groups before treatment (p=0.28), there was a trend towards decreased L4 MAT in the women randomized to the GHS1a receptor agonist as compared to placebo (Figure 1). The women randomized to relamorelin, the GHS1a receptor agonist, had significantly lower levels of acyl ghrelin after four weeks of treatment as compared to the placebo group [44]. Whether this decrease in MAT was due to decreased levels of endogenous acyl ghrelin (which may mediate MAT promoting effects through a receptor other than the GHS1a receptor) or due to other changes mediated by the GHS1a receptor agonist is unknown but warrants further study.…”
Section: Introductionmentioning
confidence: 99%